Effects of chromosomal abnormalities on pregnancy outcomes in female undergoing artificial insemination with donor's sperm. Issue 22 (4th June 2021) - Liu, Yu; Sun, Tingting; Jiang, Ronghua; Chen, Ruiling; Liu, Xiaoling; Chen, Qiao; Song, Ge
Abstract : Abstract: This study aimed to evaluate the clinical characteristics, pregnancy outcomes and prognostic factors for pregnancy of female with chromosomal abnormalities (CAs) after artificial insemination with donor's sperm (AID) treatment. A retrospective case–control study was analyzed by using the data of 29 female patients with CA and 116 controlled patients with normal karyotype (1:4 ratio) who underwent AID cycles at Guangdong Family Planning Special Hospital from January 2011 to December 2017. In all cases, reproductive histories were collected, and the cytogenetic analysis was performed by Trypsin-Giemsa banding and karyotyping. The embryos were fertilized via intracervical or intrauterine insemination. Clinical characteristic variables were compared. The prevalence of CA was found to be 0.29% in the whole AID population. The live birth rates of CA group and controlled group were 41.4% and 31.0% ( P = .29) respectively. Compared to normal karyotype group, patients with CA showed higher rate of primary infertility (93.1% vs 75.9%, P = .049); Multivariate analysis demonstrated that ovarian stimulation (odds ratio, 3.055; 95% confidence interval, 1.421–6.568; P = .004) was associated with adverse pregnancy outcomes in female patients with AID treatment. For the infertility CA patients who were phenotypically normal, AID was a suitable choice, whereas ovarian stimulation results in an improvement in the pregnancy rate.